Teachers' Attitude towards Inclusion in Vocational Education - Götzl, Mathias [Verfasser]; Driebe, Thomas [Verfasser]; Jahn, Robert W. [Verfasser] (My University, 2017)
"This paper presents a study regarding the attitude towards inclusion of teachers in vocational education. Attitude is a core component in the professional competence necessary to successfully implement inclusion. A survey was conducted measuring the attitude and relevant attitude-influencing variables, such as self-efficacy, of 62 teachers in two german federal states. The survey was used to validate a scale for measuring teachers' attitude in vocational schools via factor analysis as well as to analyze said attitude via multiple regression analysis." (Autorenreferat; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; G 2.4 Sozialer Wandel; I 2.1.1.5 Sachsen-Anhalt; I 2.1.2.6 Nordrhein-Westfalen; Berufsschullehrer; Einstellung; Inklusion; Sachsen-Anhalt; Nordrhein-Westfalen